Preventing CLABSIs among pediatric hematology/oncology inpatients: national collaborative results - Bundy, David G; Gaur, Aditya H; Billett, Amy L; He, Bing; Colantuoni, Elizabeth A; Miller, Marlene R (Pediatrics (Evanston), 2014)
Central lines (CLs) are essential for the delivery of modern cancer care to children. Nonetheless, CLs are subject to potentially life-threatening complications, including central line-associated bloodstream infections (CLABSIs). The objective of this study was to assess the feasibility of a multicenter effort to standardize CL care and CLABSI tracking, and to quantify the impact of standardizing these processes on CLABSI rates among pediatric hematology/oncology inpatients. We conducted a multicenter quality improvement collaborative starting in November 2009. Multidisciplinary teams at participating sites implemented a standardized bundle of CL care practices and adopted a common approach to CLABSI surveillance. Thirty-two units participated in the collaborative and reported a mean, precollaborative CLABSI rate of 2.85 CLABSIs per 1000 CL-days. Self-reported adoption of the CL care bundle was brisk, with average compliance approaching 80% by the end of the first year of the collaborative and exceeding 80% thereafter. As of August 2012, the mean CLABSI rate during the collaborative was 2.04 CLABSIs per 1000 CL-days, a reduction of 28% (relative risk: 0.71 [95% confidence interval: 0.55-0.92]). Changes in self-reported CL care bundle compliance were not statistically associated with changes in CLABSI rates, although there was little variability in bundle compliance rates after the first year of the collaborative. A multicenter quality improvement collaborative found significant reductions in observed CLABSI rates in pediatric hematology/oncology inpatients. Additional interventions will likely be required to bring and sustain CLABSI rates closer to zero for this high-risk population.